Update: NOVA - team, Update (World Nutrition, 2013)
Special coverage of the IUNS conference in Granada, Spain: IUNS Granada: The Bellagio Declaration on Big Food IUNS Granada: The Bellagio INFORMAS Declaration on obesity IUNS Granada: The Food System NOVA food classification Gut bugs – the bad that are good.